2023
DOI: 10.1177/10711007231166926
|View full text |Cite
|
Sign up to set email alerts
|

Does Perioperative Use of Bisphosphonate Affect the Implant Revision Rate of Total Ankle Arthroplasty?

Abstract: Background: It is unknown whether perioperative bisphosphonate (BP) use reduces revision rates in total ankle replacement arthroplasty (TAR) although its effect has been demonstrated to be effective in reducing revision rates in total knee or hip replacement arthroplasty. Methods: We reviewed National Health Insurance Service data based on national health insurance service claims data and health care utilization, health screening, sociodemographic variables, medication history, operation codes, and mortality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A few studies investigated interventions previously studied in the total knee and hip replacement literature and applied it to TAAs. In a Level III retrospective cohort study using a Korean National Health Insurance Service database with 7300 TAAs, Lee et al 27 found that perioperative bisphosphonate (BP) use did not significantly reduce revision rate. In a Level II prospective comparative study, Usuelli et al 41 found that using 8 predictive variables (BMI, state of anxiety or depression, the functional preoperative status, ankle equinus, coronal malalignment, surgical time, surgical accessory procedures, and bone quality), a fast-track recovery protocol focused on immediate weightbearing and mobilization without any plaster or boot can be applied to select TAA patients without consequence to revision rate or outcomes.…”
Section: Total Ankle Arthroplastymentioning
confidence: 99%
“…A few studies investigated interventions previously studied in the total knee and hip replacement literature and applied it to TAAs. In a Level III retrospective cohort study using a Korean National Health Insurance Service database with 7300 TAAs, Lee et al 27 found that perioperative bisphosphonate (BP) use did not significantly reduce revision rate. In a Level II prospective comparative study, Usuelli et al 41 found that using 8 predictive variables (BMI, state of anxiety or depression, the functional preoperative status, ankle equinus, coronal malalignment, surgical time, surgical accessory procedures, and bone quality), a fast-track recovery protocol focused on immediate weightbearing and mobilization without any plaster or boot can be applied to select TAA patients without consequence to revision rate or outcomes.…”
Section: Total Ankle Arthroplastymentioning
confidence: 99%